HISTORICAL-PHILOSOPHICAL CONCEPTIONS OF THE CONCEPT OF CONTRACT AND THE RULE OF LAW FOR THE NATURALIST JUS PHILOSOPHERS THOMAS HOBBES, JOHN LOCKE AND JEAN-JACQUES ROUSSEAU - Pinho de Rezende, Erickson (Revista Gênero e Interdisciplinaridade, 2023)
This work has as general objective, to seek the contribution of the philosophical foundations in the construction of the concept of State Law in the Philosophy of sec. XVI and XVII. To do so, we must also describe how Rousseau and Locke understood the right of state; To identify the influence of Rousseau and Locke in the population of his time; and, Show that the influences of these thinkers contribute in the society of today. This research will be of an eminently bibliographic nature, since it is a re-reading of the main works of each author, as well as a research to articles that deal with the subject, giving a theoretical basis for it. Nader (2014: 1) explains that “Philosophy has three classes of thinkers: philosophers, jurists and jurisfilosophists.” Already Limongi cited by Ramos; Melo; Flateschi (2015, p. 97) explains that “[...] the term Contractualism means any theory that thinks that the origin of society and political power is in a contract, a tacit or explicit agreement between those who accept to be part society and submit to that power. “ With qualitative research, they are exploratory, that is, they stimulate the interviewees to think freely about some theme, object or concept. They emerge subjective aspects and attain motivations that are not explicit, or even conscious, spontaneously. The method used will be the hypothetico-deductive, that is, science is hypothetical and provisional, not episteme or definitive knowledge, as empiricism or indutivism. In addition to the Hermeneutics of the texts of the philosophers indicated above. In analyzing the data, confront the ideas of the authors objects of study with the government and state plans that are coordinating or being developed in our society.